The Use of a Lapbook on the Founding Figures of Pancasila to Improve Students' Understanding at SDN Parsanga IV - Khairun Nisa’; Lani Susiana; Afriyatunnisa Afriyatunnisa; Yetti Hidayatillah (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
Learning Pancasila Education in elementary schools continues to face challenges due to teacher-centered instructional practices that limit students' engagement and conceptual understanding of civic learning materials. This study aimed to examine the effectiveness of a lapbook on the founding figures of Pancasila in improving third-grade students' conceptual understanding at SDN Parsanga IV, Sumenep Regency. The study employed a Classroom Action Research design consisting of two cycles, each involving the stages of planning, action, observation, and reflection. The participants were ten third-grade students, and data were collected through classroom observations, achievement tests, documentation, and field notes before being analyzed using descriptive qualitative techniques supported by descriptive quantitative learning outcomes. The findings revealed that lapbook-based learning effectively improved students' conceptual understanding, as evidenced by the increase in learning mastery from 40% before the intervention to 90% after the second cycle. Classroom observations also indicated notable improvements in students' participation, collaboration, confidence, and engagement throughout the learning process. These findings suggest that lapbook-based instruction represents an effective learner-centered pedagogical innovation for strengthening conceptual understanding and promoting active participation in elementary Pancasila Education.